East-west spatial groupings in intertidal communities, environmental drivers and key species. (25th October 2016) - Merder, Julian; Freund, Jan A.; Meysick, Lukas; Simkanin, Christina; O'Riordan, Ruth M.; Power, Anne Marie
Abstract : The rocky intertidal communities of Ireland contain a mix of cold- and warm-adapted species, however the spatial distribution of these communities has not been investigated in a systematic way. Based on a benthic community dataset collected in 2003 at 63 sites, several statistical analyses were combined with the aims of (i) detecting groups of similar communities and their spatial arrangement, (ii) relating these groups to environmental factors and (iii) identifying the species that drive the different community groups. Sørensen's index suggested two marine community groups, one of the east and south-east (termed 'east') and the other in the west, south-west and north (termed 'west'). A second partition based on combined wave exposure and sea surface chlorophyll comprised four groups, as did a further partition based on combined sea surface and air temperatures. The spatial arrangement of wave height plus chlorophyll conditions agreed reasonably well with the binary marine community partition, but the temperature partition did not. The 'east' community appeared to be associated with low wave height and chlorophyll conditions. The species that were most influential to the 'east' community were Balanus crenatus, Austrominius modestus and Fucus vesiculosus . The 'west' sites were associated with high wave height/low chlorophyll (with some variation in this due to local shelter) and the species Paracentrotus lividus, Chthamalus stellatus, Alaria esculenta and Himanthalia elongata . A longitudinal pattern rather than one associated with latitude was evident in this marine community and local drivers rather than temperature clines appeared most important for the dominant community patterns.